Dynamic analysis of a continuous-flow microwave-assisted screw propeller system for biodiesel production. (20th July 2019) - Ye, Jinghua; Zhu, Huacheng; Yang, Yang; Huang, Kama; Vijaya Raghavan, G.S.
Highlights: Biodiesel synthesis is carried out in a microwave-assisted screw propeller system. Model for biodiesel in the microwave-assisted screw propeller system is developed. The heating and reaction dynamic inside of the reactor are obtained. Many factors such as rotation speed, material composition and pitch was analyzed. The proposed reactor can be used as a large-scale preheater for chemical synthesis. Abstract: In order to overcome the apparent limitations of large-scale microwave processing, a microwave heating system with a screw propeller was utilized for biodiesel synthesis. To elucidate the heating dynamics and reaction process in the reactor, a comprehensive physics-based model was developed. A step-by-step algorithm based on implicit function, level set methods, and Arbitrary Lagrangian-Eulerian Formulation (ALE) machinery was proposed to compute the microwave heating process with chemical reaction and stirring. Material properties applied in the simulation were expressed as bivariate functions of the reaction solution's component and temperature. The temperature and reactant concentration of the microwave reactor outlet were measured and compared to simulation results to validate the simulation model. By using the proposed model, the heating process with different rotating speeds, material composition (Teflon and metal), pitch, and blade widths of the screw propeller and inlet velocities were also calculated to determine their effect on the temperature distribution of the reactor.